2014
DOI: 10.1002/mnfr.201400507
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline reduces glyceroneogenesis and induces fatty acid release in visceral adipose tissue from overweight rats

Abstract: These results demonstrate direct lipolytic and antiglyceroneogenic effects of CIT on CD and HFD AT. The selective CIT-mediated NEFA release from HFD AT was probably the consequence of the drastic decrease in glyceroneogenesis and nitric oxide was a mediator of CIT effects. These results provide evidence for a direct action of CIT on AT to reduce overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 53 publications
6
37
0
1
Order By: Relevance
“…CIT supplementation also increased energy expenditure in obese mice and, as a malate salt, improved phosphocreatine regeneration after exercise in humans . Moreover, CIT has been shown to affect lipid metabolism …”
Section: Introductionmentioning
confidence: 96%
“…CIT supplementation also increased energy expenditure in obese mice and, as a malate salt, improved phosphocreatine regeneration after exercise in humans . Moreover, CIT has been shown to affect lipid metabolism …”
Section: Introductionmentioning
confidence: 96%
“…Brown adipocytes express the uncoupling protein 1 (UCP1), which uncouples the oxidative phosphorylation from ATP production; as a result, the energy dissipates in the form of heat . Studies that examined the effect of citrulline on lipolysis showed that treatment with citrulline was effective in increasing basal lipolysis, reducing glyceroneogenesis, increasing palmitate oxidation in WAT explants, and incrementing the expression of UCP1, PPAR and PGC1‐α in young rats …”
Section: Introductionmentioning
confidence: 99%
“…By contrast, citrulline supplementation was shown to reduce visceral fat depots in old rats (Moinard et al ., ). Experiments on visceral adipose tissue explants from overweight rats showed that citrulline directly induced phosphorylation of hormone‐sensitive lipase and downregulated glyceroneogenesis, allowing an increased fatty acid release from the adipose tissue (Joffin et al ., ). Surprisingly, these effects were not observed in the present study because mice receiving citrulline alone did not show any reduction in fat mass in comparison with DIO mice.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, the metabolic adaptations induced in vivo by the combination of citrulline and atorvastatin were consistent with those observed on glucose homeostasis, visceral obesity and liver steatosis, when NO production was enhanced (Duplain et al ., ; Cook et al ., ; Schild et al ., ). Our observations on adipose tissue mass are also in agreement with those obtained in overweight rats (Joffin et al ., ). In that study, citrulline stimulated visceral adipose tissue lipolysis, and the effect was abolished by pretreatment of explants with l ‐NAME (Joffin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation